p-series - Gutiérrez-Montenegro, Marco (My University, 2017)
Estudia un tipo especial de series denominado p-series. Presenta este tipo de series y un criterio para determinar su convergencia o no.

It studies a special type of infinite series of non-negative terms called p-series. Also it presents this type of series and a test of convergence.
Keywords: Series; Convergencia